2016
DOI: 10.1016/j.jad.2016.02.013
|View full text |Cite
|
Sign up to set email alerts
|

A comparative meta-analysis of TEMPS scores across mood disorder patients, their first-degree relatives, healthy controls, and other psychiatric disorders

Abstract: Different TEMPS versions, few studies comparing BD with ADHD or BPD, no correlation with other questionnaires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 71 publications
(102 reference statements)
3
54
1
Order By: Relevance
“…and some items loaded on more than one factors to various degrees [4]. Yet, despite the number and content of the items in some short versions varied, the five-factor structure as described above was observed in different cultures including the Chinese [5,[15][16][17].…”
mentioning
confidence: 93%
“…and some items loaded on more than one factors to various degrees [4]. Yet, despite the number and content of the items in some short versions varied, the five-factor structure as described above was observed in different cultures including the Chinese [5,[15][16][17].…”
mentioning
confidence: 93%
“…7 A recent metaanalysis of the TEMPS-A by Solmi et al 8 showed that the various types of affective temperament are on the continuum, with increasing scores from healthy subjects to BD patients. Our group studied a relationship between circadian clock gene polymorphisms and temperaments as assessed by the TEMPS-A.…”
Section: Introductionmentioning
confidence: 99%
“…This interpretation is further supported by the fact that the hyperthymic temperament was negatively associated with neuroticism, which is a personality dimension consistently associated with psychopathology (Jeronimus et al, 2016). In addition, a recent meta-analysis indicates that hyperthymic temperament scores were higher in healthy controls compared to patients with mood disorder on a continuum (Solmi et al, 2016).…”
Section: For Concurrent Validity Different Dimensions Of the Temps Wementioning
confidence: 99%
“…Furthermore, it is worthy to note that that there are persuasive arguments in the literature against arbitrarily dichotomizing measures of continuous constructs (MacCallum et al, 2002). A recent systematic review and meta-analysis indicated that scores of some TEMPS-derived affective temperaments may occur on a continuum or gradient in individuals with major depressive disorder (MDD), bipolar disorder (BD), and healthy controls (Solmi et al, 2016). A dimensional approach for the TEMPS was further supported by genomewide association study that found a significant robust genome-wide association for the irritable temperament in a large sample with BD (Greenwood et al, 2012).…”
Section: Limitationsmentioning
confidence: 99%